Factors influencing the effective use of land and resource potential in Ukrainian agricultural businesses - Yavorska, Tetiana; Яворська, Тетяна Іванівна; Kurbatska, Larysa; Sitkovska, Alla; Tesliuk, Yuliia; Lukianova, Valentyna (Ukraine, Zhytomyr, 2023)
EN: Ukrainian agrarian enterprises have significant land and resource potential, but effective use of this potential depends on many factors, the study of which is of current relevance. The purpose of the research is to develop an integrated approach to changing the process of effective use of land and resource potential and to find the main determinant of its reproduction in the post-war period of economic development of the country’s agricultural sector. To achieve this purpose, mathematical tools and the income capitalisation method were applied. As a result of the study, it was established that increasing the area of land plots for growing crops that have been leased until 2025 would lead to an increase in their total size by 0.245 thousand ha in the structure of elements of reproduction and effective use of land and resource potential. Increasing the area of land of agricultural enterprises from the purchase (sale) of additional land plots will increase their value by 0.006 thousand ha, and enlarging the area of exchange land will increase by 0.377 thousand, which is a priority determinant in the structure of land and resource potential, and changes in emphyteusis will increase the total area of land plots by 0.347 thousand ha in the potential of enterprises. Thus, 97% of the variability of the area of agricultural land in the domestic market circulation will occur due to changes in the above-mentioned elements of the land determinant, which will provide for the effective use of the land and resource potential of agricultural enterprises until 2025 and augment the volume of production. The study of factors influencing the effective use of the land potential of Ukrainian agrarian enterprises has significant practical importance, as it allows identifying key factors that affect the success of agrarian enterprises, which can help them improve their strategy and find ways to improve productivity. /// UA: Аграрні підприємства України мають значний земельно-ресурсний потенціал, але ефективне використання цього потенціалу залежить від багатьох факторів, дослідження яких є актуальним. Метою дослідження є розробка комплексного підходу до зміни процесу ефективного використання земельно-ресурсного потенціалу та пошук основної детермінанти його відтворення у післявоєнний період економічного розвитку аграрного сектору країни. Для досягнення поставленої мети було застосовано математичний інструментарій та метод капіталізації доходу. У результаті дослідження встановлено, що збільшення площі земельних ділянок для вирощування сільськогосподарських культур, переданих в оренду до 2025 р., призведе до збільшення їх загального розміру на 0,245 тис. га у структурі елементів відтворення та ефективного використання земельно-ресурсного потенціалу. Збільшення площі земель сільськогосподарських підприємств від купівлі (продажу) додаткових земельних ділянок збільшить їх вартість на 0,006 тис. га, а розширення площі обмінних земель – на 0,377 тис., що є пріоритетною детермінантою в структурі земельно-ресурсного потенціалу, а зміни в емфітевзисі збільшать загальну площу земельних ділянок на 0,347 тис. га в потенціалі підприємств. Таким чином, 97 % варіативності площі сільськогосподарських угідь у внутрішньому ринковому обігу відбуватиметься за рахунок зміни вищезазначених елементів земельної детермінанти, що забезпечить ефективне використання земельно-ресурсного потенціалу сільськогосподарських підприємств до 2025 р. та нарощування обсягів виробництва продукції. Дослідження факторів, що впливають на ефективне використання земельного потенціалу аграрних підприємств України, має важливе практичне значення, оскільки дозволяє виявити ключові фактори, які впливають на успішність аграрних підприємств, що може допомогти їм удосконалити свою стратегію та знайти шляхи підвищення продуктивності.
Фактори, що впливають на ефективність використання земельно-ресурсного потенціалу в аграрному бізнесі України
Keywords: agricultural land; reproduction; economic development; monopolistic establishments; transactional circulation; землі сільськогосподарського призначення; відтворення; економічний розвиток; монополістичні утворення; трансакційний обіг